Design of tunable devices using one-dimensional Fibonacci photonic crystals incorporating graphene at terahertz frequencies. (October 2016) - Bian, Li-an; Liu, Peiguo; Li, Gaosheng
Abstract: For the one-dimensional generalized Fibonacci photonic crystals incorporating graphene, we present many valuable properties and design the tunable devices accordingly with the help of the transfer matrix method in the frequency range of terahertz. For the common structure, all of dielectric layers are cladded by graphene, we design the high-Q tunable filter with double peaks by changing the Fibonacci distribution and chemical potential. In order to reduce the crosstalk of signals through this filter, a heterostructure based on the current structure and the one without graphene is utilized to separate the two peaks. Also, we fabricate the tunable switch by altering the parity of periodic number. Besides, through cladding the graphene on the one of the dielectrics only, we obtain other two kinds of cells. Combining these cells arbitrarily as the supercell to develop the periodic structure, the number of forbidden bands is increased in accordance with certain rules so that this structure with supercell is suitable as the multi-stop filter. If the active medium is introduced, the imaginary part of the complex permittivity of the material would be negative, which means the energy amplification. For our quasi-periodic structures with active medium, the functions of chemical potential, damping constant and reference wavelength are investigated. Highlights: A high-Q tunable filter is designed based on the heterostructure. The tunable switch is gained by changing the parity of periodic number. Exploiting the deduced rules for the three kinds of graphene-embedded modes, the multi-stop filter can be fabricated. By introducing the active medium, the amplifier can be realized.